Time is brain: Review of emergency management of status epilepticus in adults - Mamta Madhiyazhagan (Current Medical Issues, 2021)
Status epilepticus (SE) is a serious complication of epilepsy that warrants both rapid and appropriate emergency management for better outcomes in terms of mortality and morbidity. The initial management of SE in emergency department (ED) involves a rapid neurological assessment and initiation of supportive therapy. Benzodiazepines are the recommended first-line treatment based on high-quality evidence, among them intramuscular (IM) midazolam IM was found to be as effective as intravenous lorazepam. However, it is important to understand that speedy drug delivery and adequate initial dose are of prime importance than selection of drug. Recent evidence shows all three second-line drugs, namely, valproate, fosphenytoin, and levetiracetam are alike in cessation of SE with similar incidence of adverse events. In refractory SE, the therapeutic options include the use of bolus dose followed by infusion of propofol, midazolam, ketamine, lacosamide, and phenobarbital. Magnesium sulfate is safe and superior in the management of eclamptic SE prompt and appropriate management in ED is the key to early cessation of SE, leading to better outcomes.